1988
DOI: 10.4319/lo.1988.33.4part2.0750
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ecology of planktonic bacteria in fresh and salt water

Abstract: The planktonic bacteria inhabiting fresh and salt waters are not physiologically identical; most marine bacteria, for example, require sodium and some marine forms can thrive at 1,000 atm of pressure in the deep sea. Despite this difference, the conclusion of this review is that the ecology of planktonic bacteria is virtually identical in fresh and salt waters.The differences are small and mostly a matter of relative proportion of various processes. That is, similar bacterial processes occur in fresh and salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 33 publications
(29 reference statements)
1
39
1
Order By: Relevance
“…Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b). These past studies, together with the observations presented here, are in stark contrast with the common assumption that terrestrially derived C is of poor nutritional quality or not particularly suited to support bacterial growth (Hobbie, 1988). The relative constancy (76 ± 6%, Figure 1) of the terrestrial signature in bacterial biomass across lakes is also remarkable given the range in lake productivity (Table 1), and in the proportion of terrestrial C consumed along this gradient (42-71%).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b). These past studies, together with the observations presented here, are in stark contrast with the common assumption that terrestrially derived C is of poor nutritional quality or not particularly suited to support bacterial growth (Hobbie, 1988). The relative constancy (76 ± 6%, Figure 1) of the terrestrial signature in bacterial biomass across lakes is also remarkable given the range in lake productivity (Table 1), and in the proportion of terrestrial C consumed along this gradient (42-71%).…”
Section: Discussioncontrasting
confidence: 51%
“…A widespread view in aquatic ecology and carbon (C) biogeochemistry is that bacterial communities exposed to a mix of algal and terrestrial compounds should develop a strategy of resource utilization whereby algal C is preferentially consumed and incorporated into biomass over terrestrial C owing to its greater accessibility and nutritional quality (Hobbie, 1988;Bianchi, 2011;Guillemette et al, 2013). However, the preferential consumption of algal C and its subsequent allocation to growth rather than to respiration remain to be empirically tested, as past studies have never simultaneously quantified the sources of DOC that support these different metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…They are often the dominant fraction in freshwater lakes, whereas they are nearly absent in the marine environment (Methé et al 1998) and have been considered as a tracer of terrigenous inputs in coastal studies (Hobbie 1988). Clone library analysis of β-Proteobacteria in a temperate latitude estuary showed that they were identical to clones from groundwater, freshwater sediments and soils (Crump et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of BSP, together with PPP in lotic ecosystems, and of the factors that affect these processes are very scarce (Hobbie, 1988;Currie, 1990;di Sierve et al, 1995), especially in Brazil. For example, the importance of rains in determining seasonality in tropical aquatic ecosystems is well known (Norris and Thoms 1999), but the effects of this functioning force upon BSP and PPP in tropical rivers are poorly understood.…”
Section: Introductionmentioning
confidence: 99%